Post-Election Economic Policy Changes: Implications and Challenges for Business in Indonesia - Aris Sarjito (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the impact of post-election economic policy changes on the business world in Indonesia, identifies challenges and opportunities, and recommends adaptation strategies for policymakers and the business world. This study uses qualitative analysis and secondary data from various theoretical perspectives, including Public Choice Theory, Economic Policy Uncertainty Theory, Institutional Theory, Transaction Cost Economics, Resource Dependency Theory, and Strategic Management Theory. This research explores the impact of post-election economic policy changes on businesses, the challenges they face in adapting, and the strategies they can use to mitigate these impacts and take advantage of opportunities. This research provides a comprehensive analysis of post-election economic policy changes in Indonesia, with a focus on strategies for the business world to face policy uncertainty and dynamic market conditions.